Competitiveness measurement model for iron mining operations - Villalva A., Juan E. (Journal of the University of Zulia, 2022)
Iron mining is an important economic activity in the world, characterized by low added value, high price volatility and high rivalry between the companies that participate in its business, where competitiveness has become a vital aspect for ensure the survival of companies, so its measurement is of special importance. On the other hand, the measurement of business competitiveness implies certain complexities, since it is a multidimensional construct and requires a methodology specially designed for it. The objective of this research was to propose a model for measuring the competitiveness of iron mining operations. To achieve this, the explanatory variables were identified and the structure of a model was designed, which represents a significant contribution to the related areas of knowledge with the management of the iron ore mining business.